CdMoO 4 synthesized by a microwave-assisted hydrothermal method and their photoluminescence and photocatality properties - De Moura, Ana P. [UNESP]; Oliveira, Larissa H.; Xavier, Camila S.; Rosa, I. L V; Li, Máximo Siu; Longo, Elson [UNESP]; Varela, José Arana [UNESP] (My University, 2012)
In this work CdMoO 4 nanoparticles were obtained under hydrothermal conditions using microwave radiation (2.45 GHz) (MH) at 100°C for different times. These powders were analyzed by X-ray diffraction (XRD), Field-emisson gum scanning electron microscopy (FEG-SEM), Ultraviolet-visible (UV-vis) absorption spectroscopy and photoluminescence (PL) measurements. XRD pattern confirmed that the pure CdMoO 4 phases were obtained. FEG-SEM powders present large-scale and homogeneous particles with microspheres-like morphology. UV-vis results were employed to determine the optical band gap these materials. Also, it showed existence of photoluminescence (PL) emission in the green wavelength range of 540-546 nm. Photocatalytic activity of CdMoO 4 nanocrystals was examined by monitoring the degradation of rhodamine B dye.
Keywords: Cadmium molybdate; Microwave-hydrothermal; Photocatality; Photoluminescence; FEG-SEM; Hydrothermal conditions; Hydrothermal methods; Microwave hydrothermal; Microwave-assisted; Photocatalytic activities; Photoluminescence emission; Photoluminescence measurements; Rhodamine B dye; Wavelength ranges; XRD patterns; Cadmium; Degradation; Dyes; Exhibitions; Films; Nanocrystals; Nanotechnology; Photocatalysis; Powders; Scanning electron microscopy; X ray diffraction; X ray powder diffraction; Nanocomposite films